Molecular detection of hemoplasmas in domestic cats from different Brazilian regions - Clara Morato Dias; Kamila Pinheiro Francisco; Gabriela Veiga Oliveira; João Vitor dos Santos Alves da Silva; Eliz Oliveira Franco; Daniel Antônio Braga Lee; Dália Monique Machado Ribeiro; Maria Eduarda Chiaradia Furquim; Mayra Araguaia Pereira Figueiredo; Rosangela Zacarias Machado; Marcos Rogério André (Revista Brasileira de Parasitologia Veterinária)
Abstract Domestic cats can be parasitized by Mycoplasma haemofelis, ‘Candidatus Mycoplasma haemominutum’, and ‘Candidatus Mycoplasma turicensis’. Although the molecular occurrence of hemoplasmas in domestic cats has been investigated in the five geographical regions of Brazil, no studies have been conducted in the states of Rondônia and Minas Gerais to date. The present work aimed to investigate the molecular occurrence of hemoplasmas in cats from four Brazilian states in the Northern, Central-Western and Southeastern regions of the country. Among 486 blood samples – 80 from Rondônia (RO), 100 from Goiás (GO), 155 from Minas Gerais (MG), and 151 from São Paulo (SP) – submitted to the endogenous gapdh gene-based PCR, 94.44% (459/486) were positive, of which 1.96% (9/459; 1 from RO, 2 from GO, 5 from MG, and 1 from SP) were positive in the qPCR assay for hemoplasmas based on the 16S rRNA gene. In the phylogenetic analyses, the obtained 16S rRNA (two genotypes) and 23S rRNA (three genotypes) sequences were positioned together with ‘Candidatus Mycoplasma haemominutum’. The present study showed the first molecular evidence of infection by hemoplasmas in cats from MG and RO, contributing to a better understanding of the epidemiology of feline hemoplasmosis agents in Brazil.